2015
DOI: 10.1186/s12888-015-0388-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age differences in couples on depressive symptoms: evidence from the Korean longitudinal study of aging (2006–2012)

Abstract: BackgroundDepression represents one of the most common psychiatric disorders among older adults. Married couples are affected frequently, and psychiatric problems usually affect marital satisfaction. Despite the frequency of such relationships, it appears that very few studies have examined the issues that arise in couples of this type of marriage. Therefore, we investigate whether age differences between couples affect extent of depressive symptoms among older adults.MethodsOur analysis included 2,881 couples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(24 reference statements)
0
12
2
Order By: Relevance
“…Compared with the general demography of age differences, it was difficult to assess the characteristics of couples because of differences in the age distributions. In a recent report, an age difference between couples was associated with increased depression symptoms . We could not obtain a statistically significant association between decision‐makers hoping to undergo NIPT and the age difference.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Compared with the general demography of age differences, it was difficult to assess the characteristics of couples because of differences in the age distributions. In a recent report, an age difference between couples was associated with increased depression symptoms . We could not obtain a statistically significant association between decision‐makers hoping to undergo NIPT and the age difference.…”
Section: Discussioncontrasting
confidence: 67%
“…In a recent report, an age difference between couples was associated with increased depression symptoms. 17 We could not obtain a statistically significant association between decision-makers hoping to undergo NIPT and the age difference. We reported that the higher mental distress scores were associated with women whose partners were the primary decisionmakers.…”
Section: Discussionmentioning
confidence: 72%
“…The long-standing poor economic state of Nigeria has heightened the postponement of marriage among men [ 16 ]. This age gap in marriage poses several problems: for instance, there may be differences in maturity and differences in opinions; the partners’ sexual life may be affected at a later stage, if husband is much older than the wife; early planning for children might be necessary if husband is much older; ageing and early widowhood are also problems associated with a wide spousal age gap [ 17 , 18 ]. It is always possible that a couple may influence each other to adopt new interests, but an age gap in the relationship can compromise this.…”
Section: Introductionmentioning
confidence: 99%
“…This research builds on the relatively sparse literature about age-heterogenous partnerships. Prior research has shown that fairly few differences in mental and physical health exist between individuals in age-heterogenous versus age-homogenous partnerships (Choi and Vasunilashorn 2014;Drefahl 2010;Kim et al 2015). Previous research has also shown that the demographic characteristics of individuals in age-heterogenous versus age-homogenous relationships are distinct: The former (regardless of gender or age) (Coles and Francesconi 2011;Esteve et al 2009;England and McClintock 2009;Feighan 2018;Gustafson and Fransson 2015), few have examined whether individuals in these partnerships differ from those in agehomogenous relationships on gender attitudes, relationship quality, and sex life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, widowed respondents who were previously in an age-heterogenous relationship had somewhat worse mental health than their widowed counterparts who had been in age-homogenous relationships (Choi and Vasunilashorn 2014). However, the 2006-to-2012 Korean Longitudinal Study of Aging shows that depressive symptoms are higher for men and women in marriages in which the wife is older than the husband (Kim, Park, and Lee 2015). In terms of death rates, Danish register systems-which comprehensively document characteristics of the entire populationshow that net of other controls, women had higher mortality rates if they were either older or younger than their husband compared to women who were within one year of their husband's age (Drefahl 2010).…”
Section: Physical and Mental Healthmentioning
confidence: 97%